2021
DOI: 10.1093/rheumatology/keab307
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phospholipid antibodies do not predict damage in SLE patients in the 21st century—an observational study from the Lupus-Cruces cohort

Abstract: OBJECTIVE To compare the influence of antiphospholipid antibodies (aPL) on global and cardiovascular damage in patients with systemic lupus erythematosus (SLE) diagnosed before and after year 2000. METHODS 286 patients from the Lupus-Cruces cohort with a minimum follow-up of 5 years, divided into two sub-cohorts according to the date of diagnosis, before 2000 (<2000) and from 2000 on (≥2000). We compared the mean SDI sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…The persistent use (at least 75% and 100% of follow-up time) of antiplatelets, statins, antihypertensives and hydroxychloroquine (HCQ) during the 3-year follow-up period was included in the univariate analysis, but no statistical significance was demonstrated for any of these treatments (online supplemental table 2). HCQ has been shown to prevent thrombotic cardiovascular events in several retrospective and prospective studies in SLE, and especially its long duration 13 47 48. In our study, HCQ use was not found to have a protective role against subclinical atherosclerosis progression.…”
Section: Discussioncontrasting
confidence: 57%
“…The persistent use (at least 75% and 100% of follow-up time) of antiplatelets, statins, antihypertensives and hydroxychloroquine (HCQ) during the 3-year follow-up period was included in the univariate analysis, but no statistical significance was demonstrated for any of these treatments (online supplemental table 2). HCQ has been shown to prevent thrombotic cardiovascular events in several retrospective and prospective studies in SLE, and especially its long duration 13 47 48. In our study, HCQ use was not found to have a protective role against subclinical atherosclerosis progression.…”
Section: Discussioncontrasting
confidence: 57%
“…Further, thrombogenic microparticles have been reported to be induced by aPL [ 75 ]. Another aspect of this type of aPL effect is complement activation, which may promote thrombosis though mechanisms need to be elucidated more [ 76 , 77 , 78 ].…”
Section: Apl and Cvd In Slementioning
confidence: 99%
“…Even though aPL and APS remain an important cause of CVD including thrombosis in SLE, recent studies indicate that improved treatment, with hydroxychloroquine, life‐long anticoagulant treatment, statins, and optimization of prednisolone treatment, has considerably improved prognosis and thus other causes of CVD in SLE become relatively more important [ 78 ].…”
Section: Apl and Cvd In Slementioning
confidence: 99%